Urine drug screening in a forensic mental health population: frequency and clinical utility in risk management - Penney, Stephanie R. (The journal of forensic psychiatry & psychology, 2021)
There is a high frequency of urine drug screens performed within forensic patient populations, at significant use of resources and without firm evidence of utility in identifying prohibited substance use, assisting in risk management, or reducing other adversities. This study describes the clinical practice of urine drug testing in a large forensic psychiatric service in Ontario, Canada, and aims to determine the period prevalence of substance use in this setting. Over a three-month period, there were 1493 tests performed in 132 patients, representing 50.4% of patients surveyed and 31.1% of all active patients. Ten percent of urine samples retuned positive for a prohibited substance (most commonly cannabis or alcohol) while a similar proportion were dilute. Although inpatients received double the number of tests as compared to outpatients, they were less likely to return positive. Patients with positive test results were more likely to receive frequent testing, suggesting that clinical teams often employ urine drug screening to monitor those at highest risk for ongoing use, rather than as a method of deterrence or therapeutic intervention. Implications for the continued use of urine drug screening in this patient population, as well as recommendations to better tailor their use, are discussed.